Grafting of acrylonitrile onto crosslinked polystyrene - 296194 Shahida Ibrahim; Ahmedy Abu Naim, supervisor; Fakulti Sains (2006)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2006